2017
DOI: 10.1037/edu0000146
|View full text |Cite
|
Sign up to set email alerts
|

Making connections: Replicating and extending the utility value intervention in the classroom.

Abstract: We replicated and extended prior research investigating a theoretically guided intervention based on expectancy-value theory designed to enhance student learning outcomes (e.g., Hulleman & Harackiewicz, 2009). First, we replicated prior work by demonstrating that the utility value intervention, which manipulated whether students made connections between the course material and their lives, increased both interest and performance of low-performing students in a college general education course. Second, we exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
270
8
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(303 citation statements)
references
References 91 publications
13
270
8
12
Order By: Relevance
“…Another study, conducted in two large sections of an introductory psychology course, found that the utility-value intervention increased final exam scores and interest in psychology for all students on average and for students who performed poorly on initial exams in particular (Hulleman et al 2017). In addition, they found that the utility-value intervention had the strongest positive effects for the students who were most at risk in this context, males who performed poorly on initial exams.…”
Section: Task Value Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study, conducted in two large sections of an introductory psychology course, found that the utility-value intervention increased final exam scores and interest in psychology for all students on average and for students who performed poorly on initial exams in particular (Hulleman et al 2017). In addition, they found that the utility-value intervention had the strongest positive effects for the students who were most at risk in this context, males who performed poorly on initial exams.…”
Section: Task Value Interventionsmentioning
confidence: 99%
“…Hulleman and colleagues’ (2010, 2017) work in large introductory psychology courses demonstrates that the utility-value intervention can be effective for struggling students, including groups of students who tend to underperform. This raises the possibility that the utility-value intervention can address achievement gaps.…”
Section: Task Value Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the Expectancy-Value Theory, it is proposed that the environment's efforts to influence task value will have an effect on students' achievements (Atkinson, 1957;Eccles et al, 1983;Wigfield, 1994;Wigfield & Eccles, 1992). In this sense, several interventions have shown its positive effects on the task value perceived by individuals (Harackiewicz, Rozek, Hulleman, & Hyde, 2012;Hulleman, Godes, Hendricks, & Harackiewicz, 2010;Hulleman & Harackiewicz, 2009;Hulleman, Kosovich, Barron, & Daniel, 2016;Lee Johnson & Sinatra, 2013;Pang, 2014;Rozek, Hyde, Svoboda, Hulleman, & Harackiewicz, 2014;Schukajlow et al, 2012).…”
Section: Introductionmentioning
confidence: 99%